CLIMATE CHANGE SCENARIOS AND THEIR IMPACTS ON DAIRY PRODUCTION IN SOUTHERN BRAZIL - Oliveira, Z. B.; Silva, C. M.; Souza, I. J.; Link, T. T.; Bottega, E. L. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The present work had as objective to analyze scenarios of climatic changes and their impacts on milk production in the South of Brazil. The study was performed for twelve municipalities in the southern region of Brazil, with four municipalities in each state: Paraná, Santa Catarina and Rio Grande do Sul. The Temperature and Humidity Index (ITU) was calculated for the situation of maximum thermal discomfort months of summer), from the maximum air temperature (Tmax) and the minimum relative air humidity (URmin). The meteorological data used as reference for the "current scenario" were obtained from INMET. For the creation of climate change scenarios, 0.5ºC, 1,5ºC and 3º C were added in Tmax (averages from the period 1961-1990) and the reduction of URmin was calculated in these scenarios. In the current climatic situation, the ITU is higher than 72, considered critical for dairy cow production, in all evaluated municipalities and throughout the period (December to March), reaching extreme values of 84 in the state of RS. Current caloric stress is improved in the + 0.5ºC scenario, due to the reduction of URmin that compensates for the increase in Tmax; remain in the scenario of + 1.5ºC and increases in the scenario + 3.0ºC, where the decline in milk production is on average 70% higher than in the current climatic situation.